2016
DOI: 10.1016/j.ijantimicag.2016.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to chlorhexidine amongst multidrug-resistant clinical isolates of Staphylococcus epidermidis from bloodstream infections

Abstract: 12Emergence of Staphylococcus isolates with reduced susceptibility to chlorhexidine is being 13 increasingly reported. We present an update to a previous report showing continuing efficacy 14 of chlorhexidine-based infection control measures against Staphylococcus aureus over six 15 years. We screened qacA/B genes in Staphylococcus isolates collected over another six 16 years in the same intensive therapy unit in Scotland where chlorhexidine baths form an 17 essential component of long-term control of nosocomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 30 publications
4
24
0
Order By: Relevance
“…In addition, resistance to CHX is increasing and although cross‐resistance to antibiotics remains controversial, some studies indicate that the overall exposure to CHX increases the risk for resistance to some antibiotics . Furthermore, the resistance to CHX has resulted in some outbreaks and healthcare‐associated infections . In our study, CHX+ aPDT demonstrated better bactericidal effect than CHX alone against P. gingivalis on titanium surfaces.…”
Section: Discussionmentioning
confidence: 52%
“…In addition, resistance to CHX is increasing and although cross‐resistance to antibiotics remains controversial, some studies indicate that the overall exposure to CHX increases the risk for resistance to some antibiotics . Furthermore, the resistance to CHX has resulted in some outbreaks and healthcare‐associated infections . In our study, CHX+ aPDT demonstrated better bactericidal effect than CHX alone against P. gingivalis on titanium surfaces.…”
Section: Discussionmentioning
confidence: 52%
“…A more recent Scottish study included 25 S. epidermidis isolates obtained between 2007 and 2014 from a single hospital intensive care unit, and it showed a chlorhexidine tolerance rate of 12% by agar dilution assay. In both studies, there was an association between increased chlorhexidine tolerance and the carriage of qacA/B genes (231,232).…”
Section: Chlorhexidinementioning
confidence: 85%
“…Previous studies have characterized three alleles of qacA : qacA1 , qacA2 , and qacA3 (18, 21). Additional studies, however, have suggested clinical and environmental Staphylococcus isolates may carry novel alleles of qacA (30, 31). Our identification of multiple novel qacA alleles supports this suggestion that considerably more qacA allelic variation exists within human staphylococcal populations than previously appreciated.…”
Section: Discussionmentioning
confidence: 99%